KEGIATAN ASISTENSI MENGAJAR DI SDN 7 CAKRANEGARA: MENINGKATKAN KOMPETENSI CALON GURU SEKOLAH DASAR - Ardani, Refika; Amini, Aulina Asti; Yuli Haeni; Baiq Madina Hasanah; Tantori Adsa Hidayat (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
Teaching assistance is a student activity in supporting the learning process at school through direct involvement in intracurricular, extracurricular activities, supervision, and Wiyata Mandala. This activity was carried out at SDN 7 Cakranegara, Mataram City, which has a comfortable learning environment and supports collaboration. This article reflects the experience of teaching assistance and its impact on improving student competence as prospective teachers. Intracurricular activities include the preparation of teaching materials and implementation of learning, while extracurricular activities include art training and preparation of farewell events. Supervision is carried out through guidance and evaluation by supervising lecturers and mentor teachers. Wiyata Mandala includes activities that support school culture such as training in ceremonies and planting medicinal plants. The implementation takes place for one semester through the preparation, implementation, and reporting stages. The results show that active student involvement in schools can improve pedagogical, professional, social, and personality competence as prospective educators.